Feasibility study of worker safety at highway emergency lane - Mustaffa, Musfirah; Mohammad Hisyammudden, Muhammad Syahmi; Hassan, Suhaimi; Jumari, Mohamad Zhairul Iqumal; Mat Nadir, Mohamad Amirul; Yusof, N M; Ikhsan, M S; Ismon, Maznan; Zakaria, Hanis; Yusof, M S; Nik Aziz, Nik Nazmi Amir; Hakim, Mohd Farizwan Azmil; et al. (2023)
Safety procedures at highways are essential to ensure safe, clean and accessible roads and highways. The workers were often exposed to hazardous situations, as seen by numerous accidents involving highway workers on the road in recent years. Safety technologies in the highway construction work zone may help improve the roadway construction and maintenance workers’ safety. This paper reviews the statistics of road accidents in Malaysia, highway work zone safety problems and existing applications of safety sensor systems as an improvement of safety technology in the construction work zones. As an improvement towards the safety technology, Signal Warning Detector (SWAD) system was developed to increase the safety at highway work zone especially on PLUS highways in Malaysia. The development of the SWAD system’s parameter setting was discussed later in the methodology section of this paper